Implementation Of A Combination Of Stream Cipher Algorithm And Rotate 13 For Data Security - Ikhsan Tri Mukrozi; Sapri Sapri; Abdussalam Al Akbar (Jurnal Komputer, Informasi dan Teknologi, 2024)
The issue of data security and confidentiality is one of the important aspects of data, messages and information. Stream Cipher is often referred to as a stream cipher. The advantage of this method is that it is relatively faster in the encryption-decryption process and is also not limited by the length of the plaintext. ROT13 is a substitution cipher encryption by shifting characters forward 13 times, counting 1 character in front of it, and shifting characters based on the order of characters in the ASCII table. By combining the Stream Cipher and ROT13 algorithms, it produces a method that can provide a better level of security compared to the application of each of these methods separately. The results of the analysis and testing carried out using different decryption keys resulted in the ciphertext cannot be returned which shows normal things because the method used is symmetrical cryptography so that the decryption process can only be done using the same key as the key during decryption.